Behind the lighthouse effect - Tito Boeri; Pietro Garibaldi; Marta Ribeiro (Institute for the Study of Labor (IZA), 2010)
A large body of empirical literature indicates that, contrary to predictions from economic theory, wages in the informal sector increase after any minimum wage hike. This phenomenon was so far explained as a byproduct of a signal conveyed by statutory minimum wages to wage setting in the informal sector, as if workers in the latter had significant bargaining power. A simple matching model shows that the lighthouse effect may be induced by significant sorting and composition effects between the formal and shadow sectors in the aftermath of the increase in the minimum wage. Using data on Brazil, we test this alternative explanation of the lighthouse effect, associated with the endogenous sorting of workers by skill in the formal and informal sectors. We find that sorting accounts for at least one third of the increase in average wages in the informal sector after the minimum wage hike. This contribution of sorting to wage dynamics in the informal sector is also increasing over time.
Keywords: J30; 330; Minimum wage; lighthouse effect; sorting; Lohnbildung; Informeller Sektor; Mindestlohn; Arbeitsmarkt; Matching; Qualifikation; Schätzung; Brasilien